COMPARISON ANALYSIS OF THE HEALTH OF SHARIA COMMERCIAL BANKS AND CONVENTIONAL COMMERCIAL BANKS - Ekaningsih, Lely Ana Ferawati; Susanti, Nawal Ika; Sa'adah, Irma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This research uses a quantitative approach with a comparative research type. The sample selection in this study used a non-probability sampling method which was purposive sampling with the following criteria: financial banking which has two sharia and conventional systems, financial banking which issued 10 consecutive financial statements, financial statement banking which had the highest assets in 2011-2020, and banks whose financial statements whose profit and loss present data on outstanding shares and share prices. The results of the study show that: four financial ratios of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR, Good Corporate Governance (GCG) Return On Assets (ROA), and Capital Adequacy Ratio (CAR), analyzed there is 1 (one) financial ratios that have the ability to distinguish significantly, namely the CAR ratio, because it has been proven by obtaining a significant value below 0.05, while the other 2 (two) financial ratios do not have the ability to distinguish (not discriminator ) significantly between Islamic banking and conventional Islamic banking groups, including LDR and ROA, this is evidenced by obtaining a significant value above/greater than 0.05. In addition, it also shows that the soundness of conventional banking is better than the financial performance of Islamic banking.